2013
DOI: 10.17221/6862-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism identification in goat DGAT1 and STAT5A genes and association with milk production traits

Abstract: Polymorphisms of DGAT1 and STAT5A genes in Xinong Saanen and Guanzhong goat breeds were investigated. PCR-RFLP, SSCP, and DNA sequencing were used to identify three SNPs: DQ380250:g.407_408insC in the DGAT1 gene, AJ237937:g.6798C>T and g.6852C>T in the STAT5A gene. In DGAT1 g.407_408insC locus, the frequencies of C -allele were 0.79-0.85, and frequencies of C + allele were 0.21-0.15. At STAT5A g.6852C>T locus, frequencies of C allele were 0.70-0.72, and frequencies of T allele were 0.30-0.28. Compared with goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
(20 reference statements)
1
11
0
Order By: Relevance
“…The distribution of genotypes was in Hardy-Weinberg equilibrium (χ 2 =1.017, df=1, P=0.313). The lack of TT genotype was also reported by An et al [16] in Xinong Saanen and Guanzhong breeds. A very low frequency of TT individuals was subsequently reported by Wu et al [17] in Xinong Saanen and Hainan black populations.…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…The distribution of genotypes was in Hardy-Weinberg equilibrium (χ 2 =1.017, df=1, P=0.313). The lack of TT genotype was also reported by An et al [16] in Xinong Saanen and Guanzhong breeds. A very low frequency of TT individuals was subsequently reported by Wu et al [17] in Xinong Saanen and Hainan black populations.…”
Section: Resultssupporting
confidence: 77%
“…The allelic frequencies found in Garganica goat breed were similar to those observed in Hainan black breed and, interestingly, the frequency of the C allele is higher if compared with the frequency of allele T in all the investigated samples. An et al [16] studied the association among genotypes at STAT5A/Eco81I locus and milk performance traits of animals: the does with CT genotype have greater milk yield than those carrying CC genotype (P<0.05). Moreover, Wu et al [17] found a positive relationship among STAT5A/Eco81I polymorphism and some phenotypic traits.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations